2019
DOI: 10.48550/arxiv.1907.12604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conduction properties of extended defect states in Dirac materials

Francesco Romeo

Abstract: We demonstrate the existence of localized states in close vicinity of a linear defect in graphene. These states have insulating or conducting character. Insulating states form a flat band, while conducting states present a slowdown of the group velocity which is not originated by many-body interactions and it is controlled by the interface properties. For appropriate boundary conditions, the conducting states exhibit momentum-valley locking and protection from backscattering effects. These findings provide a c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These states are localized in close vicinity of the interface and have been proposed as possible nucleation centers of correlated states in graphene. The existence of zeroenergy flat band states with insulating character has also been demonstrated 18 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These states are localized in close vicinity of the interface and have been proposed as possible nucleation centers of correlated states in graphene. The existence of zeroenergy flat band states with insulating character has also been demonstrated 18 .…”
Section: Introductionmentioning
confidence: 94%
“…In Ref. 18 it has been demonstrated that localized defect states with conductive character can nucleate in close vicinity of a linear defect of a Dirac material. Such states, under appropriate circumstances, can exhibit protection from back-scattering events due to the momentum-valley locking.…”
Section: Analysis Of the Current Density At The Interfacementioning
confidence: 99%